The value of 18F-NaF PET/CT in the diagnosis of bone metastases in patients with nasopharyngeal carcinoma using visual and quantitative analyses - Wang, Dong; Li, HaiWen; Guo, ChengMao; Huang, Shisang; Guo, XuFeng; Xiao, JingXing (Frontiers in Bioengineering and Biotechnology, 2022)
To assess the diagnostic value of 18F-NaF PET/CT in diagnosing bone metastases in patients with nasopharyngeal carcinoma (NPC) using visual and quantitative analyses. 164 patients with NPC who underwent 18F-NaF PET/CT between 2017 and 2021 were included. The sensitivity, specificity, and accuracy were calculated. All bone lesions were divided into metastatic bone lesion group and benign lesion group; the benign lesion group was further subdivided into benign lesion without osteophyte and fracture group (CT images showing no osteophyte, no fracture), and benign lesion with osteophyte and fracture group (CT images showing typical osteophytes and fractures), the differences in maximum standardized uptake value (SUVmax) were compared between every two groups, and the diagnostic cut-off values were derived from receiver operating characteristic curves (ROC). Quantitative data were expressed as mean ± SD, multiple continuous variables were compared using one-way analysis of variance (ANOVA), and multiple comparisons among more than two groups were made using the Bonferroni method. The sensitivity, specificity, and overall accuracy of 18F-NaF PET/CT for the diagnosis of bone metastases in NPC were 97.1%, 94.6%, and 95.1% based on the patient level and 99.5%, 91.5%, and 96.4% based on the lesion level, respectively. The SUVmax was significantly different between the metastatic bone lesion group and the benign lesion without osteophyte and fracture group (p < 0.05); the area under the curve was 0.865, the threshold was 12.5, the sensitivity was 0.912, and the specificity was 0.656. Visual analysis of 18F-NaF PET/CT has high sensitivity and specificity for diagnosing bone metastases in NPC. After excluding osteophytes and fracture lesions based on CT findings, using SUVmax ≥12.5 as the threshold can be an important reference for the differential diagnosis of bone metastases and benign bone lesions in patients with NPC.